Eco Kids, Ano 5, Número 10, Julho de 2012, Ilhéus/BA - (:unkn) unknown (Ministério Público do Estado da Bahia, 2012)
No abstract.
Keywords: Educação ambiental; Meio Ambiente; Reciclagem; Animal marinho; CNPQ::CIENCIAS SOCIAIS APLICADAS::DIREITO